Imparare dagli errori: apprendenti russofoni di italiano LS/L2 - Masla, Alina (Educazione Linguistica Language Education, 2021)
The study deals with written errors in Italian language made by Russian learners and their use in Italian LS/L2 lessons. The cultural-linguistic background of Russian learners of Italian and the differences in the morphosyntax of Italian and Russian are partly accounted for causes of such errors. The paper focuses on the didactic advantages of ranking multiple choice test on the base of the degree of incorrectness of the proposed choice: it supports the importance of using systematic errors as a source to create ad hoc multiple choice, and to trigger students’ conscious second language learning.